Modulation of miR-26a-5p and miR-15b-5p Exosomal Expression Associated with Clopidogrel-Induced Hepatotoxicity in HepG2 Cells - Freitas, Renata C. Costa de; Bortolin, Raul H.; Lopes, Mariana B.; Tamborlin, Letícia; Meneguello, Letícia; Silbiger, Vivian N.; Hirata, Rosario D. C.; Hirata, Mário H.; Luchessi, Augusto D.; Luchessi, André D. (Frontiers in Pharmacology, 2017)
Clopidogrel is an essential antiplatelet drug used to prevent thrombosis complications associated with atherosclerosis. However, hepatotoxicity is a potential adverse effect related to clopidogrel therapy. Exosome-derived miRNAs may be useful for improved monitoring of drug response and hepatotoxicity risk. In the present study, the expression of several exosomal miRNAs (miR-26a-5p, miR-145-5p, miR-15b-5p, and miR-4701-3p) and cell-derived mRNA targets (PLOD2, SENP5, EIF4G2, HMGA2, STRADB, and TLK1) were evaluated in HepG2 cells treated with clopidogrel (6.25, 12.5, 25, 50, and 100 µM) for 24 and 48 h. Then, clopidogrel cytotoxicity was evaluated by analyzing DNA fragmentation and the cell cycle profile using flow cytometry. Differential expression of exosome-derived miRNAs and cell-derived mRNAs was analyzed by RT-qPCR. Exposure of HepG2 cells to high concentrations of clopidogrel (50 and 100 µM) for 24 h caused significant DNA fragmentation (17.6% and 44.4%, respectively; p < 0.05) and 48 h (26.8% and 48.9%, respectively; p < 0.05), indicating cellular toxicity. Upregulation of miR-26a-5p and downregulation of miR-15b-5p was observed in cells exposed to 100 μM clopidogrel for 24 and 48 h. The miR-26a-5p target mRNAs HMGA2, EIF4G2, STRADB, and SENP5 were downregulated in HepG2 cells following exposure to cytotoxic concentrations of clopidogrel (50 and 100 µM) for 24 h, and HMGA2 levels remained low after 48 h of treatment. TLK1, a target of miR-15b-5p, was downregulated by 50 and 100 µM clopidogrel at 24 h. In conclusion, our results suggest that exposure to high concentrations of clopidogrel modulates the expression of exosomal miR-26a-5p and miR-15b-5p and their target mRNAs in HepG2 cells. Dysregulation of these miRNAs maybe modulate the regulatory pathways involved in clopidogrel-induced liver injury.